Antonio Conselheiro pelo olhar do outro e por ele mesmo: uma análise discursiva da (des)construção de sua imagem - Oliveira, Ilza Carla Reis de (2018)
The Canudos war is the subject of many studies and publications and the figure of Antonio Conselheiro emerge diverse interpretations. This historical fact still constitutes a vast material for study, especially in the linguistic scope. In this sense, the present research, of bibliographical character, part of the discourses around the central character of the movement of Belo Monte and aims to realize a counterpoint between its image constructed by the look of the other and the image constructed by its own look. In the first case, in order to compose the corpora of the research, the first news about him, published by newspapers of the time, is taken as materiality: one from the newspaper O Rabudo, the first to refer to the figure of Antonio Conselheiro in 1874, another of the Diário da Bahia, dated June 27, 1876, and the last of the Diário de Notícias, published almost two decades later, on May 31, 1893. In addition to the news, two cordel poems, entitled "Defending Counselor "and" Perez Pillow ", written fifty years after the end of the Canudos war by the Euclidean poet and writer José Aras. In the second case, an analysis is made of six of the Counselor's handwritten preaching, recorded in two books found after the end of the conflict: three from the book of 1895 and three from the book of 1897. The purpose is to analyze how discourses work make reference to the leader of Belo Monte, since they emerge of discursive subjects and specific conditions of production. This work is based, therefore, on the French Discourse Analysis, proposed by Michel Pêcheux. In order to compose the theoretical-analytical device, it was mainly based on the notion of Imaginary Formations. The analyzes point out that the different discursive subjects are interpellated by different ideological formations and, therefore, affiliated to different discursive formations. This is because, as ADP pecheutiana advocates, the imaginary formations that the protagonists of these discourses have of their place and of the place of their interlocutor intervene directly in the conditions of the production of discourse, thus focusing on what is said, how it is said and, consequently, in the effects of meaning that emerge from these sayings. This explains why the image of Antonio Conselheiro is negative for the newspapers, while for the cordelista subject, affiliated with another ideology, occupying a different place of saying, that is, the religious leader is a martyr and hero. At another point, the preachings are taken to analyze the image of the Counselor from his own point of view, the discursive subject, from the imaginary representation of the social place from which he speaks, has the image of humble servant and mouthpiece of the Word of God and guardian of the true religion of the Good Jesus.